Relationships between Plant Diversity and Grasshopper Diversity and Abundance in the Little Missouri National Grassland - David H. Branson (Psyche: A Journal of Entomology)
A continuing challenge in orthopteran ecology is to understand what determines grasshopper species diversity at a given site. In this study, the objective was to determine if variation in grasshopper abundance and diversity between 23 sites in western North Dakota (USA) could be explained by variation in plant species richness and diversity. In this system with relatively low plant diversity, grasshopper species richness and abundance were not significantly associated with plant species richness in either year. Although a number of significant associations between plant diversity and grasshopper diversity were found through regression analyses, results differed greatly between years indicating that plant species richness and diversity did not lead to strong effects on grasshopper diversity metrics. Plant species richness appears to be too coarse grained to lead to accurate predictions of grasshopper species richness in this system dominated by generalist grasshopper species.